(untitled) - Harlay, John P. (Boston, MA, 2005)
Laboratory Exercises in Microbiology, 6/e has been prepared to accompany Prescott et al's "Microbiology, 6/e". Like the text, the laboratory manual provides a balanced introduction to laboratory techniques and principles that are important in each area of microbiology
TT. Vi sinh vật học
Keywords: Microbiology,Vi sinh